Challenges Faced by Health Professionals in Obtaining Correct Medication Information in the Absence of a Shared Digital Medication List - Unn Sollid Manskow; Truls Tunby Kristiansen (Pharmacy, 2021)
Information about patient medication use is usually registered and stored in different digital systems, making it difficult to share information across health care organisations. The lack of digital systems able to share medication information poses a threat to patient safety and quality of care. We explored the experiences of health professionals with obtaining and exchanging information on patient medication lists in Norwegian primary health care within the context of current digital and non-digital solutions. We used a qualitative research design with semi-structured interviews, including general practitioners (n = 6), pharmacists (n = 3), nurses (n = 17) and medical doctors (n = 6) from six municipalities in Norway. Our findings revealed the following five challenges characterised by being cut off from information on patient medication lists in the current digital and non-digital solutions: ‘fragmentation of information systems’, ‘perceived risk of errors’, ‘excessive time use’, ‘dependency on others’ and ‘uncertainty’. The challenges were particularly related to patient transitions between levels of care. Our study shows an urgent need for digital solutions to ensure seamless, up-to-date information about patient medication lists in order to prevent medication-related problems. Future digital solutions for a shared medication list should address these challenges directly to ensure patient safety and quality of care.